Dampak Kualitas Layanan dan Persepsi Harga Terhadap Kepuasan dan Loyalitas serta Peran Moderasi Gender (Studi Kasus Pada Nasabah Bank BRI di Yogyakarta) - Rinaldi, Rinaldi (Journal Competency of Business, 2021)
The purpose of this study is to determine and explain the effect of service quality on customer satisfaction (customer satisfaction); to determine and explain the effect of price perception on customer satisfaction (customer satisfaction); to determine and explain the effect of customer satisfaction (customer satisfaction) on customer loyalty (customer loyalty) and to determine and explain the effect of customer satisfaction (customer satisfaction) on customer loyalty (customer loyalty) moderated by gender. The sampling method that will be used is the non-probability sampling method. In this study, samples were obtained that were not planned, but by chance, which were available to researchers at the time of data collection (convenience sampling). The number of samples specified in the study was 300 people, this has fulfilled the assumption of using SEM and the limitations of time and cost. The sample in this study is BRI Bank customers in Yogyakarta. Analysis tool using SEM analysis with AMOS program. The results showed that service quality had an effect on customer satisfaction (customer satisfaction); price perception has an effect on customer satisfaction (customer satisfaction); customer satisfaction affects customer loyalty and gender affects the relationship between customer satisfaction and customer loyalty